GERAKAN NII KARTOSOEWIRJO (KW IX) - Asep Zaenal Ausop (Jurnal Sosioteknologi, 2009)
NII (The Indonesian Islamic State) called DI (Dar al-Islam) is an Islamic movement organization (Harakah IslÃ¡miyyah) is led by Maridjan Sekarmadji Kartosoewirjo (MSK), a prominent of Masyumi from West Java. This organization has its own soldiers called TII or The Islamic Indonesian Soldiers. They proclaimed "The Indonesian Islamic State "“ The Blessing State of Allah (NKA- NII) on August 7th 1949. DI / TII had been destroyed by TNI (The National Military) with the various ways. MSK has been caught on June 4th 1962 and executed on September 5th in the same year. Most of Indonesian people believe that NII was dead. But in 1999, Indonesian people were surprised by encouragence of the new NII identified as NII Commandemant Area IX or called NII KW IX, by the Highest Commander named Abu Toto Abdussalam. This research proved that, after the death of MSK, NII had been separated into many factions including the faction of Abu Toto Abdussalam. Refering to David Krech and Zanden's theory about the factors which influence conflict of human groups, is that one of causes of separation, is the different norms and values of the beliefs. This cause also happened in NII. However, as de facto and de jure, NII KW IX was the development of NII MSK. Although the two organizations ( NII) have the same objective to establish the Indonesian Islamic State, they have many differences in doctrines and movement strategies. keywords : NII, KW IX, Bai'ah, Al-Kahfi.